Highly efficient maximum power point tracking using DC–DC coupled inductor single-ended primary inductance converter for photovoltaic power systems. Issue 9 (20th October 2016) - Quamruzzaman, M.; Mohammad, Nur; Matin, M.A.; Alam, M.R.
Abstract : Solar photovoltaics (PVs) have nonlinear voltage–current characteristics, with a distinct maximum power point (MPP) depending on factors such as solar irradiance and operating temperature. To extract maximum power from the PV array at any environmental condition, DC–DC converters are usually used as MPP trackers. This paper presents the performance analysis of a coupled inductor single-ended primary inductance converter for maximum power point tracking (MPPT) in a PV system. A detailed model of the system has been designed and developed in MATLAB/Simulink. The performance evaluation has been conducted on the basis of stability, current ripple reduction and efficiency at different operating conditions. Simulation results show considerable ripple reduction in the input and output currents of the converter. Both the MPPT and converter efficiencies are significantly improved. The obtained simulation results validate the effectiveness and suitability of the converter model in MPPT and show reasonable agreement with the theoretical analysis.